Pemanfaatan Buah Nanas Dan Kelopak Bunga Rosella Dalam Pembuatan Fruit Leather (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
The purpose of the study was to get the best combination of pineapple fruit and roselle flower in making fruit leather. The research used a Complete Randomized Design (CRD) with 5 treatments and 3 replications.The treatment was the ratio of pineapple and roselle petal puree namely NR1 (100:0), NR2 (90:10), NR3 (80:20), NR4 (70:30) and NR5 (60:40).The data obtained were analyzed statistically using Anova and DNMRT at 5% level. The research showed that rasio of pineapple fruit pureeand roselle flower puree showed significant effect on moisture, content, ash content, degree of acidity (pH), reduction sugar content, antioxidant activity content and organoleptic test. The best treatment of fruit leather from this research wasNR5 which was water content 11,24%, ash content 0,32%, degree of acidity (pH) 2,90, reduction sugar content 34,84%, antioxidant activity content 95,447 µg/ml. Has a red color, roselle scented, sour taste, the texture rather springy and preferred by the panelist for overall assessment.Keywords :fruit leather, pineapple puree and roselle petals puree